2007
DOI: 10.1002/hup.856
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effects between rupatadine 10 mg and placebo on actual driving performance of healthy volunteers

Abstract: Rupatadine 10 mg is not sedating and does not impair driving performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 44 publications
1
22
0
1
Order By: Relevance
“…53 The effects of RU on driving were evaluated in a study performed on healthy human volunteers, and was compared with 50mg hydroxyzine or placebo. 54 Driving performance was assessed using a standard highway test, standard deviation of the lateral position, Stanford sleepiness scale, driving quality scale and rate of sedation. There was no difference between RU and placebo, whereas driving performance was impaired by hydroxyzine.…”
Section: Central Nervous System Cognitive and Psychomotor Effectsmentioning
confidence: 99%
“…53 The effects of RU on driving were evaluated in a study performed on healthy human volunteers, and was compared with 50mg hydroxyzine or placebo. 54 Driving performance was assessed using a standard highway test, standard deviation of the lateral position, Stanford sleepiness scale, driving quality scale and rate of sedation. There was no difference between RU and placebo, whereas driving performance was impaired by hydroxyzine.…”
Section: Central Nervous System Cognitive and Psychomotor Effectsmentioning
confidence: 99%
“…A mixed gender study showed that levocetirizine 5 mg had no acute or subchronic effect on SDLP (Verster et al 2003). The effects of rupatadine in its therapeutic dose of 10 mg (Vuurman et al 2007) were also comparable to those of placebo treatment. Bilastine was tested in 20 and 40 mg doses, both after acute dosing and repeated doses, and was found not to cause driving impairment in any of these dosing conditions (Conen et al 2010).…”
Section: Second Generation Antihistaminesmentioning
confidence: 76%
“…Hydroxizine 50 mg acutely impaired driving performance, with an SDLP increase larger than the effect of a BAC of 0.8 g/L (Vuurman et al 2007). After 8 days of treatment with hydroxizine 50 mg driving performance was still impaired, but to a lesser extent (Conen et al 2010).…”
Section: First Generation Antihistaminesmentioning
confidence: 98%
“…Although other approaches such as 'off-road' driving simulators or 'overthe-road' driving tests can be used to assess unwanted CNS side effects, it has been suggested that they are less sensitive to sedative effects, particularly in the case of antihistamines [50,51]. In addition, laboratory tests may provide more information of a more practical value with respect to drug effects in demanding real-life situations than more 'real' experimental settings [33].…”
Section: Discussionmentioning
confidence: 99%